2018
DOI: 10.1111/and.12958
|View full text |Cite
|
Sign up to set email alerts
|

A possible direct action of oxytocin on spermatogenesis and steroidogenesis in pre-pubertal mouse

Abstract: The aim of this study was to evaluate the effects of in vivo and in vitro treatments of oxytocin (OT) on the testis of pre-pubertal mice. The OT treatment produced significant changes in the spermatogenic and steroidogenic activity by increasing expression of OT-receptor in the testis of pre-pubertal mice. Treatment with OT showed increased proliferation of germ cells as indicated by increased number of spermatocytes and round spermatids. Dose-dependent increase in expression of PCNA, Bcl-2 and AR proteins was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…Several studies have demonstrated the marked expression of OTRs in Leydig (interstitial) cells, principal cells of the epididymal epithelium and also the smooth muscle of the male reproductive tract and accessory sex glands in rodents, rabbits, ruminants, humans and stallions (Assinder et al., 2000; Stadler et al., 2020; Watson et al., 1999). This expression of oxytocin within the testis and epididymis has been reported as being associated with spermatogenesis (Anjum et al., 2018) and increased of sperm transport in rams (Nicholson et al., 1999). Oxytocin, thus, acts as a paracrine and endocrine factor that binds with a high affinity to OTRs on Leydig and Sertoli cells, epithelial cells of the epididymis and peritubular smooth muscle cells in sheep, humans, macaque monkeys and horses (Frayne & Nicholson, 1998; Watson et al., 1999; Whittington et al., 2001).…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Several studies have demonstrated the marked expression of OTRs in Leydig (interstitial) cells, principal cells of the epididymal epithelium and also the smooth muscle of the male reproductive tract and accessory sex glands in rodents, rabbits, ruminants, humans and stallions (Assinder et al., 2000; Stadler et al., 2020; Watson et al., 1999). This expression of oxytocin within the testis and epididymis has been reported as being associated with spermatogenesis (Anjum et al., 2018) and increased of sperm transport in rams (Nicholson et al., 1999). Oxytocin, thus, acts as a paracrine and endocrine factor that binds with a high affinity to OTRs on Leydig and Sertoli cells, epithelial cells of the epididymis and peritubular smooth muscle cells in sheep, humans, macaque monkeys and horses (Frayne & Nicholson, 1998; Watson et al., 1999; Whittington et al., 2001).…”
Section: Introductionmentioning
confidence: 79%
“…This study firstly demonstrated the expressions of OTRs in the testis, cauda epididymis and vas deferens of tom cats. The presence and localization of these receptors in the testis and efferent ducts reflect the essential roles of oxytocin in spermatogenesis (Anjum et al., 2018) and sperm transport (Frayne et al., 1996; Kunz et al., 2007; Thackare et al., 2006). Immunohistochemical localization of OTRs in reproductive tracts of male animals has been revealed in several studies such as in mice (Ang et al., 1991; Assinder et al., 2002), rats (Foo et al., 1991), rams (Assinder et al., 2000), dogs (Dalmazzo et al., 2019) and stallions (Jung & Yoon, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Testicular OT may have a role to play in the reproductive processes of the male by influencing the production of gonadal steroids. OT was found to stimulate testosterone production in mice [7], as well as in goats and pre-pubertal rats [8,9]. In cell experiments of rat Leydig cells, OT also has the foundation to stimulate testosterone production [10].…”
Section: Oxytocin and Its Receptors In Physiology 21 Male Reproductive Tissuesmentioning
confidence: 98%
“…The data of Liu et al (2019) indicted that oxytocin is particularly regulating the transmission of sperm from the epididymis by elevating its level in peripheral circulation, which may cause a significant increase in sperm conveyance that takes place through ejaculation. In mice, Anjum et al (2017) found that oxytocin treatment caused morale changes in the spermatogenic and steroidogenic efficacy by raising expression of oxytocin receptors in the testicles before the Puberty in mice, also, treated mice with oxytocin raised the germ cells as a result to increase the number of spermatocytes, It was observed that pre-puberty mice treated with a higher dose of oxytocin had a higher concentration of testosterone. Furthermore, El-Badry et al (2013) suggested that injection oxytocin before semen collection in rams may be beneficial leading to the increase in the semen ejaculation and increase in the total number sperm in frozen semen, Also, repeated injection of oxytocin did not cause any side effect on the fineness of semen in all cases, whether fresh or frozen, add to the action of antioxidants or sperm plasma and testosterone grade in the rams.…”
Section: Male Reproductive Tractmentioning
confidence: 99%